(untitled) (Revista Brasileira Multidisciplinar, 2026)
This study analyzed the characteristics of artisanal food processing carried out by family farmers from two organic producer associations located in the municipalities of Angatuba and Buri, São Paulo, Brazil. The objective was to understand the cultural and technical dimensions involved in this activity, as well as to identify the challenges and opportunities related to strengthening processing as a rural development strategy. The research was conducted through semi-structured questionnaires applied to participating families and technical visits to production units. The results indicated that artisanal food processing, although not the main productive activity of the families, plays an important role in complementing income and adding value to products that are traditionally sold in natura. Furthermore, this activity reflects traditional knowledge and cultural practices that contribute to the appreciation of family farming and local food security. However, barriers such as inadequate infrastructure and high costs for obtaining sanitary registrations were identified as recurring challenges. The study concludes that encouraging the expansion of food processing can be a promising pathway to promoting sustainable rural development, integrating economic, social, cultural, and environmental dimensions. Strengthening public policies and initiatives aimed at technical and financial support is recommended to overcome barriers and maximize the benefits of this practice for rural communities.